Formative applications of ongoing visual inspection for trial‐based functional analysis: A proof of concept. Issue 4 (15th July 2021) - Standish, Cassandra M.; Bailey, Kathryn M.; Lambert, Joseph M.; Copeland, Bailey A.; Banerjee, Ipshita; Lamers, Mallory E.
Abstract : Trial‐based functional analysis (TBFA) possesses many strategic advantages which make it an ideal candidate for adoption in applied settings. Notwithstanding, some aspects of the analysis remain underdeveloped, including structured guidelines for interacting with obtained data reliably in formative and summative ways. The purpose of this study was to adapt existing ongoing visual‐inspection (OVI) criteria to match the idiosyncrasies of TBFA and then to assess their practical utility in applied settings. Thus, we first drafted OVI criteria appropriate for trial‐based FA (i.e., TB‐OVI). Then, we trained 5 caregivers to conduct TBFAs of their children's challenging behavior and to react to their data as they obtained it, using the TB‐OVI criteria as their guide. Finally, we validated interpretations of TBFA outcomes based on TB‐OVI criteria through effective intervention. Across 5 participants and 7 opportunities, function‐based interventions successfully eliminated challenging behavior.